Application of maximum principle optimizing active current subharmonic filter - V. N. Anosov; D. N. Belkova; V. M. Kaveshnikov (Омский научный вестник, 2019)
In this article, the structure and parameters of an optimal regulator for active filter current subharmonics (AFSC) are received based on the optimal control method L. S. Pontryagin. Such a regulator allows one to achieve complete suppression of the subsynchronous torsional vibrations of the rotors of gas turbine units (GTU) of an autonomous power plant at the stage of emergence and growth of resonance at one of the natural frequencies of GTU torsional vibrations and to prevent operation of vibration protection and emergency shutdown of the power plant. Such outages lead to large economic and technological losses.